Анализа корелације нивоа ФЦАС1, прокалцитонина и СЦИА25 у серуму са прогнозом пацијената са сепсом: Нивои серума ФЦАС1, прокалцитонина и СЦИА25 у прогнози сепсе. - Yang, Yanhong; Hua, Yali; Yuan, Jing; Chen, Qingmei (Journal of Medical Biochemistry, 2026)
Objective To explore the levels of serum Familial Cold Autoinflammatory Syndrome 1 (FCAS1), Procalcitonin, and Small Inducible Cytokine A25 (SCYA25) in patients with sepsis caused by drug-resistant Klebsiella pneumoniae (KP) infection and their relationship with prognosis. Methods The study group consisted of 410 patients who were hospitalized to our hospital between March 2019 and March 2024 and had sepsis brought on by KP. A total of 196 drug-resistant patients with sepsis caused by KPs were classified into the drug-resistant group, and 214 nondrug-resistant patients with sepsis caused by KPs were classified into the nondrug-resistant group. According to the severity of sepsis, 410 patients with KP-induced sepsis were divided into a severe sepsis group (178 patients) and a sepsis group (232 patients). The control group consisted of an additional 410 healthy volunteers who were examined physically at our hospital throughout the same time period. It was established that drug-resistant KPs were resistant to clinical medications. The prognosis of patients with drug-resistant sepsis caused by a KP infection was split into a survival group and a death group 28 days after admission. Serum FCAS1 levels were detected via an enzyme-linked immunosorbent assay, and serum Procalcitonin and SCYA25 levels were determined via the chemiluminescence method. The diagnostic value of serum FCAS1, Procalcitonin, and SCYA25 for drug-resistant KP-induced sepsis as well as their predictive value for the mortality of patients with drug-resistant KP-induced sepsis were examined using receiver operating characteristic (ROC) curves. Multivariate logistic regression analysis was used to investigate the factors impacting death in patients with sepsis and drug-resistant KP infection. Results A total of 250 drug-resistant KP strains were detected in 196 patients with sepsis caused by drug-resistant KPs. The resistance rates of these strains to cefazoline, ceftriaxone, ceftazidime, amtronam, imipenem and meropenem were greater than 90%. Serum FCAS1, Procalcitonin, and SCYA25 levels exhibited a statistically significant difference (P<0.05) between the severe sepsis group and the control and sepsis groups. Additionally, the sepsis group’s levels were higher than those of the control group. Serum FCAS1, Procalcitonin, and SCYA25 levels were considerably higher in the drug-resistant group than in the nondrug-resistant group (P<0.05). The nonsurviving group had higher levels of serum FCAS1, Procalcitonin, SCYA25, Acute Physiology and Chronic Health Evaluation II (APACHE II), and infection-related Organ Failure Assessment (SOFA) ratings than the surviving group, while the nonsurviving group’s serum ALB level was lower (P<0.05). Patients with drug-resistant KP infection and sepsis had higher serum levels of FCAS1, Procalcitonin, and SCYA25, which were risk factors for death, according to multivariate logistic regression analysis (P<0.05), whereas elevated levels of serum ALB were protective factors for death in patients with drug-resistant KP infection and sepsis (P<0.05). The results of the ROC curve analysis revealed that the areas under the curve (AUCs) of serum FCAS1, Procalcitonin, and SCYA25 and the combined diagnosis of drug-resistant KP infection sepsis were greater than those of FCAS1, Procalcitonin and SCYA25 (P<0.05), and the AUCs of the combined prediction of the three indicators for the death of patients with drug-resistant KP infection sepsis were greater than those of FCAS1, Procalcitonin and SCYA25. The AUC was calculated separately (P<0.05). Conclusion The levels of serum FCAS1, Procalcitonin and SCYA25 in patients with drug-resistant KP-induced sepsis are relatively high. The combined detection of these three indicators has high diagnostic value for drug-resistant KP-induced sepsis and is related to the death of patients.